2019
DOI: 10.2217/fvl-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Hepatitis B Virus Infection On Semen Parameters of Fertile Men

Abstract: Aim: To investigate the effect of chronic hepatitis B virus (CHB) infection on semen parameters of males with proven fertility. Material & methods: 61 fertile men with CHB infection and a control group of 42 HBV-negative fertile men were assessed for serum and semen HBV viral loads by quantitative real-time PCR, complete semen analysis, hypo-osmotic swelling test, seminal total peroxide, total antioxidant capacity assay and sperm DNA integrity evaluation. Results: CHB men demonstrated significantly lower s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Many viruses, such as hepatitis C virus (HCV), hepatitis B virus (HBV), human immunodeficiency virus (HIV), herpes simplex virus, and cytomegalovirus (CMV), can cause male infertility (6). Several studies in Iran have indicated that CMV and HBV infections play a major role in male infertility (2,7). It has been reported that CMV can be extracted from almost all body secretions, including vaginal and cervical secretions, seminal fluid, oropharyngeal secretions, and milk, as well as stool, urine, and blood (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many viruses, such as hepatitis C virus (HCV), hepatitis B virus (HBV), human immunodeficiency virus (HIV), herpes simplex virus, and cytomegalovirus (CMV), can cause male infertility (6). Several studies in Iran have indicated that CMV and HBV infections play a major role in male infertility (2,7). It has been reported that CMV can be extracted from almost all body secretions, including vaginal and cervical secretions, seminal fluid, oropharyngeal secretions, and milk, as well as stool, urine, and blood (8).…”
Section: Introductionmentioning
confidence: 99%
“…HBV transmits via genital secretions and sexual contact. This virus was established to disrupt sperm parameters and release inflammatory cytokines (7). Inflammatory cytokines are induced in the early phase of viral infections.…”
Section: Introductionmentioning
confidence: 99%